An Investigation of Water Quality Status in Gebeng Industrial Estate, Pahang, Malaysia - Islam, Mir Sujaul; Sobahan, Md Abdus; R. M., Yunus (Environment Conservation Journal, 2015)
Gebeng is a rapidly growing industrial area in Pahang, Malaysia. The study was conducted to explore the pollution level and to find out the human interference on surface water quality. The highly polluted parameters were BOD, COD, DO, ammonical nitrogen, phosphate, Pb, Cu, Cd, Co and As and most of the stations categorized as polluted (Class III and IV). Heavy metals like Pb, Cu, Co, Cd and As were higher at upstream river zone and highly polluted nevertheless the downstream zone and surface water were comparatively less polluted. Industrial wastes and effluents increased the contamination levels of the studied water.